Faecal oestrone, rather than an androgen, is a sensitive and consistent marker of male reproductive state in equids - A.M. Burton; J.A. Britnell; G.K. Davies; S. Shultz (Theriogenology Wild)
Measuring faecal steroid hormones can provide important information on reproductive state, health, and population demographics of wild and threatened species. Androgens are indicators of male reproductive state, dominance, and can provide sex and age metadata to samples. Steroids are difficult to measure in faeces, however, due to metabolism prior to excretion and to cross-reactivity. It is therefore essential to ensure faecal assays reflect biologically meaningful changes before using them in ecological settings. We assessed the suitability of four potential faecal biomarkers of male reproductive state in three equids: Grevy’s zebra (Equus grevyi), Mountain zebra (Equus zebra) and Carneddau Mountain ponies (Equus ferus caballus). We used commercial enzyme immunoassays for three androgens: androstenedione, testosterone, epiandrosterone, and an androgen derived oestrogen, oestrone, to evaluate variation between reproductively mature and immature males. Surprisingly, faecal oestrone showed the best discrimination between male reproductive classes in all species, with higher Z-scores in reproductive males compared to foals. Neither faecal testosterone, androstenedione, nor epiandrosterone could discriminate between reproductive classes. We also observed seasonal variation in Carneddau pony stallions preceding the breeding season for oestrone and androstenedione, and found high individual variation in repeated samples from Grevy’s zebra. Finally, we compared faecal oestrone between stallions and mares; non-pregnant mares had lower oestrone than stallions but there was only a significant difference between stallions and pregnant females in Grevy’s zebra. Our results suggest that faecal oestrone, rather than an androgen, is a more optimal biomarker of male reproductive state in equids. Our study highlight the importance of ensuring faecal steroid measurements are biologically and ecologically meaningful within wildlife endocrinology.